Impact of Dividend Policy on Shareholders’ Wealth: An Empirical Analysis of Listed Insurance Companies in Pakistan - MUHAMMAD SHABEER KHAN; DR. SAID SHAH; SYEDA UROOJ BABER (Journal of Business & Tourism, 2021)
This study aims to investigate the impact of dividend policy on shareholders’ wealth using secondary data of 17 listed insurance companies in Pakistan employing non-probability convenience sampling for 2012-2015. Shareholders’ wealth is used as dependent variable measured by earning per share whereas dividend policy as independent variable measured by three ratios namely dividend per share, Retention ratio and dividend payout ratio. Analysis techniques include descriptive statistics, regression analysis and correlation analysis. The results show that all the independent variables impact dependent variable positively with dividend per share and retention ratio significant at 5%. Moreover study reveals that the theory of dividend irrelevancy failed in the case of insurance industry of Pakistan.